1993
DOI: 10.5271/sjweh.1490
|View full text |Cite
|
Sign up to set email alerts
|

Lobe of origin of lung cancer among asbestos-exposed patients with or without diffuse interstitial fibrosis.

Abstract: KARJALAINEN A, ANTTILA S, HEIKKILA L, KYYRONEN P, VAINIO H. Lobe of origin of lung cancer among asbestos-exposed patients with or without diffuse interstitial fibrosis. Scand J Work Environ Health 1993; 19:102-7. The effect of asbestos exposure and asbestos-associated fibrosis on the lobe of origin of lung cancer was studied among 108 lung cancer patients. The asbestos-exposed patients had significantly more lower lobe tumors than the unexposed patients. Similar results were obtained when occupationalhistory o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
9
2
2

Year Published

1994
1994
2006
2006

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 18 publications
4
9
2
2
Order By: Relevance
“…For these exposures, the most dominant increase in the risk has been reported for adenocarcinoma (2, 49,50).…”
Section: Discussionmentioning
confidence: 99%
“…For these exposures, the most dominant increase in the risk has been reported for adenocarcinoma (2, 49,50).…”
Section: Discussionmentioning
confidence: 99%
“…For example, among the 15,477 histologically proven cases of primary lung cancer among white men in the Surveillance, Epidemiology, and End Results (SEER) Study, 65% of the tumors originated in the upper lobes compared with 35% in the middle or the lower lobes (10). Among asbestos-exposed individuals, some studies have reported an inversion of this ratio, with a higher proportion of tumors occurring in the lower lobes (12)(13)(14)(15)(16)(17)(18)(19)(20). For example, in a study of 108 patients undergoing lobectomy or pneumonectomy for lung cancer, 62% of asbestos-exposed patients had lower-lobe tumors, in contrast to 25% of the nonexposed patients (p Ͻ 0.0001) (19).…”
mentioning
confidence: 99%
“…Such national reference values are important in Finland, as 40% of the asbestos used during the past several decades consisted of anthophyllite (2), a variety of asbestos of only minor importance in other industrialized countries. There is increasing knowledge on the pulmonary fiber concentrations of Finnish lung cancer and mesothelioma patients, but the number of reference cases representing the general population is small (3)(4)(5).…”
mentioning
confidence: 99%